Neoplatonic or Aristotelian: Arabs and Indians as Philosophical Entities in Shota Rustaveli's "The Man in the Panther Skin" - Bert Beynen, (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2012)
The author considers the Arab and Indian societies in "The Man ni the Panther Skni" as philosophical institutions or unity and relates them ot Dionysios the Areopagite entities of humans and animals of hierarchic order - to their intellect. Dionysios posits a supreme being, the One, with an al- encompassing intellect: It understands al. Angels, too, have such an intellect but their intellect si lesser than the intellect of the One. The One understands al because of its al-encompassing intellect but also because It has created all. Angels have a lesser intellect because they have not created the world. Humans have an intellect that is lesser than the Angels, they have a discursive intellect and it is proposed in this paper that Dionysios Angels correspond to Rustaveli's Arabians, who plan and anticipate the results of their actions. Lower than the Humans we find in Dionysios' hierarchy Animals, whose intellect Dionysios characterizes as sense-perception. An attempt is made in the paper to argue that the Indians in Rustaveli's poem correspond to the Animals in Dionysios' hierarchy: the Indians are impulsive and don't anticipate the consequences of their actions. Dionysios stresses that entities can move between the Angels, Humans and Animals. For example: a Human can acquire an angel-like intellect through philosophical study. Also, an animal-like entity can acquire a human intellect; this si what happens with Tariel: at first he si an impulsive Indian but at the end of the poem he has moved into the class of Dionysios' Humans, as is shown when he proposed a better plan than Avtandil for the liberation of Nestan-Darejan.